Construction of scientific thinking from a didactic sequence in sociology teaching - Piunti, Juliana (Revista Hipótese, 2018)
This paper presents an experience of teaching practice in the area of Sociology, and aims to share a didactic sequence developed with the first year of integrated high school and discuss the possibility created for the construction of scientific thinking with students. All stages of pedagogical practice were recorded so that it could be analyzed later: the choice of the suicide theme, the use of Durkheim’s theory of social fact, the expository class, the monitoring of the research activity carried out by the students and the evaluation of the process. It was based on the assumption that the students’ data collection on juvenile suicide and the articulation of these data with Durkheim’s theory of social fact would allow students to overcome common-sense perspectives on the phenomenon investigated. The evaluation of the final textual productions of the students allowed to identify a more elaborated analysis of the fact investigated, when compared to the first textual productions previously realized by the same students.